Flipbook Media Based on Problem-Solving to Improve Fifth Grade Students’ Learning Outcomes in Pancasila Education - I Made Dimas Erlangga Adi Putra; AA Gede Agung; Komang Alit Wahyuni (Undiksha Press, 2025)
The lack of utilization of instructional media has led to low student learning outcomes in Pancasila education. This study aims to examine the effectiveness of a problem-solving-based flipbook learning media in Pancasila education on students’ learning outcomes. The development research employed the ADDIE model, involving fifth-grade elementary school students and expert reviewers as research subjects. Data collection methods used in this study included questionnaires and tests, with data analyzed through descriptive quantitative techniques and inferential statistics. The results of the study, based on a one-sample t-test, showed a calculated t-value of 9.726 and a critical tvalue of 1.717, indicating that H₀ is rejected and H₁ is accepted. It can be concluded that the problem-solving-based flipbook learning media is effective for use in the Pancasila education content on National Events Surrounding the Proclamation of Independence for fifth-grade students. This study implies that the use of problem-solving-based flipbook media effectively improves student learning outcomes, and therefore, teachers should integrate interactive media to create more meaningful and contextual learning experiences.